Waiting for the domino effect: interview by Fiona Fleck. - Daube, Michael (2012)
This month, landmark legislation comes into force in Australia, making it the first country to ban branded cigarette packaging. Mike Daube talks to Fiona Fleck about how public health campaigning has come a long way since the 1970s.